Hybrid HDPE/MCM-41 nanocomposites: crystalline structure and viscoelastic behaviour - Cerrada, María L. (2013)
Polyethylene-based nanocomposites have been prepared by in situ polymerisation of ethylene with mesostructured MCM-41 within a large range of nanofiller concentrations. The structural, thermal and viscoelastic studies have shown that the use of mesoporous MCM-41 as catalyst carrier and its further presence in the final material is an effective route for the successful attainment of nanocomposites. Data shows that minimal changes in crystallinity are observed but crystallites become thicker as MCM-41 content is raised in the nanocomposites. A confinement effect is found and a delay in the crystallisation process of the macrochains within pores and channels is observed. These novel self-reinforced nanocomposites present an enhanced rigidity, which becomes more important as temperature is raised. Accordingly, they exhibit an improved mechanical performance without varying the final processing temperature since Tm is the same for all of the specimens. In agreement with other works, it is confirmed that the MCM-41 acts as promoter for polyethylene degradation, an easier degradability being observed in these nanocomposites.